Financial Risks, Stability, and Globalization - Johnson, Omotunde (International Monetary Fund, 2002)
This book covers financial sector stability issues in the following areas: risk management and governance in financial institutions; financial crises and contagion; domestic monetary and financial policies; and international cooperation. The papers were presented at the IMF's eighth Central Banking Seminar by authors from academia, investment banks, government, and international institutions. The papers discuss such subjects as bank soundness, systemic bank restructuring, and the safety and efficiency of systemically important payment systems and their interaction with the macroeconomic environment.